Retrospective Study of Effectiveness of Homoeopathic Constitutional Remedies in Treating Children with Delayed Speech - Salim, Saira Mohammed; SathishKumar, V; CV, Chandraja; P R, Sisir; N V, Sugathan (International Research in Medical and Health Sciences, 2021)
Background: Speech is a valid conventional communication method, an action in which language is expressed with verbal symbols of language. Speech development is considered by experts to be a useful indicator of a child’s overall development and cognitive ability and it is also related to school success. If not managed properly, speech delay may impact a person’s life personally, socially, academically, and vocationally for years to come. Objective: To demonstrate the efficiency of homoeopathic constitutional remedies in cases with delayed speech, to understand the other co-existing developmental and behavioural disorders, to understand commonly using remedies. Method: The study was a retrospective study conducted in the host institution. Data are collected from Medical Records Department, cases reported between 2015-2019. The study population was selected by considering the OPD cases coming to the “Sarada Krishna Homoeopathic Medical College Developmental Screen Chart. Results: Most reported cases were males and the most reported age is 4 years. Mostly prescribed medicine was Calcarea group medicine and almost all cases show good improvement. Mostly given potency is 200, based on the susceptibility of the children. Conclusion: Some parents don’t aware of the normal milestones of a child. If it is not managed properly it will affect the overall development of the child. Our homoeopathic remedies are very effective in treating these cases by individualising the person and by prescribing constitutional remedies.